Charitable Giving and Nonbinding Contribution-Level Suggestions - Evidence from a Field Experiment - Maja Adena; Steffen Huck; Imran Rasul (Center for Economic Studies and ifo Institute (CESifo), 2014)
When asking for donations, charitable organizations often use suggestions concerning the amount of potential contributions. In our randomized field experiment, opera visitors received solicitation letters asking to support a social youth project organized by the opera house. The three different treatments were: no suggestion and suggestions of 100 and 200, respectively. The findings are that suggestions substantially influence the distribution of donations received. The mean amounts given increase significantly. The increase is stronger in the 200 treatment. On the other hand, the participation rate decreases if a suggestion is made. Overall, the returns from the campaign increase non-significantly.
Keywords: C93; D12; D64; 330